Human Tau Expression Does Not Induce Mouse Retina Neurodegeneration, Suggesting Differential Toxicity of Tau in Brain vs. Retinal Neurons - Rodriguez, Léa; Mdzomba, Julius Baya; Joly, Sandrine; Boudreau-Laprise, Mélissa; Planel, Emmanuel; Pernet, Vincent (Frontiers in Molecular Neuroscience, 2018)
The implication of the microtubule-associated protein (MAP) Tau in the ocular manifestations of Alzheimer’s disease (AD) is elusive due to the lack of relevant animal model. However, signs of AD have been reported in the brain of transgenic mice expressing human Tau (hTau). To assess whether hTau is sufficient to induce AD pathogenesis in the retina as well, in the present study, we compared the retinal structure and function of mice deprived of Tau (mTKO) with those of transgenic mice expressing hTau (hTau). Our results revealed that hTau is particularly abundant in the inner nuclear layer cells of the retina. By electroretinogram (ERG) recording, light-induced retinal cell activation was not altered in hTau compared with mTKO littermates. Surprisingly, the ERG response mediated by cone photoreceptor stimulation was even stronger in hTau than in mTKO retinae. Immunofluorescent analysis of retinal sections allowed to observe thicker inner retina in hTau than in mTKO eyes. By Western blotting, the upregulation of mTOR that was found in hTau mice may underlie retinal structure and function increases. Taken together, our results not only indicate that hTau expression is not toxic for retinal cells but they also suggest that it may play a positive role in visual physiology. The use of hTau may be envisaged to improve visual recovery in ocular diseases affecting the retinal function such as glaucoma or diabetic retinopathy.